2022
DOI: 10.1186/s12888-022-04399-9
|View full text |Cite
|
Sign up to set email alerts
|

Risky or protective? Online social support’s impact on NSSI amongst Chinese youth experiencing stressful life events

Abstract: Background This study was designed to investigate potential gender differences in the interrelations between different types of stressful life events and non-suicidal self injury (NSSI) among Chinese youth, as well as to test the direct and moderating impacts of online social support on Chinese students’ NSSI engagement under the pressure of different types of stressful life events. Methods Based on the data of 2200 students from middle - highschoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Gender difference: Gender difference in NSSI is not a static gap, but evolves across time, widening in mid-adolescence and disappearing by early adulthood ( 44 ). Moye Xin, et al ( 45 ) investigated potential gender differences in the interrelations between different types of stressful life events and non-suicidal self injury (NSSI) among Chinese youth, clarifying the risk factors in affecting NSSI from male and female perspectives respectively. Fang Cheng, et al ( 46 ) in their study found that in the path analysis model with the introduction of mediating effects, the influence of gender differences on NSSI behavior becomes more pronounced under the interaction of multiple factors: women seem to be more significantly influenced by the external derivatives in the internal derivatives than male subjects, and are more likely to trigger NSSI behavior under the interaction of multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…Gender difference: Gender difference in NSSI is not a static gap, but evolves across time, widening in mid-adolescence and disappearing by early adulthood ( 44 ). Moye Xin, et al ( 45 ) investigated potential gender differences in the interrelations between different types of stressful life events and non-suicidal self injury (NSSI) among Chinese youth, clarifying the risk factors in affecting NSSI from male and female perspectives respectively. Fang Cheng, et al ( 46 ) in their study found that in the path analysis model with the introduction of mediating effects, the influence of gender differences on NSSI behavior becomes more pronounced under the interaction of multiple factors: women seem to be more significantly influenced by the external derivatives in the internal derivatives than male subjects, and are more likely to trigger NSSI behavior under the interaction of multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…Model 3 (M/F) incorporated online social support (OSS) as an independent variable to assess its direct impact on the relationship between perceived life stress (independent variable) and mental health conditions (dependent variable). Following Model 3, interaction terms for different types of perceived life stress (punishment, learning pressure, loss, interpersonal relationships, and adaptation) were successively introduced in Models 4–8 to explore the potential moderating effects of online social support on mental health [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…NSSI (Non-suicidal self-injury) refers to deliberate self-inflicted damage to one’s own body tissue by methods such as cutting, scratching, and self-hitting that leads to tissue damage, without conscious suicidal intent and for reasons not socially sanctioned. NSSI is commonly used among youth as a method of dealing with painful emotions and thoughts ( Xin et al, 2022 ) and can have varying degrees of negative consequences. It is a prevalent health concern among university students, given that they are twice as likely to engage in NSSI than their nonuniversity attending peers are ( Swannell et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%